Simulation of Train-Turnout Coupled Dynamics Using a Multibody Simulation Software - Albert Lau; Inge Hoff (Modelling and Simulation in Engineering)
With the advancements of computing power, multibody simulation (MBS) tool is used to study not only train dynamics but also more realistic phenomena such as train-track coupled dynamics. However, train-turnout coupled dynamics within MBS is still hard to be found. In this paper, a train-turnout coupled model methodology using a MBS tool GENSYS is presented. Dynamic track properties of a railway track are identified through numerical receptance test on a simple straight track model. After that, the identified dynamic track properties are adopted in a switch and crossing (turnout) to simulate train-turnout coupled dynamic interaction including parameters such as rail bending stiffness and sleeper mass variation along the turnout. The train-turnout coupled dynamic interaction is compared to the dynamic interaction simulated from a widely accepted moving mass train-turnout model. It is observed that the vertical and lateral normal forces for the new train-turnout coupled model and the conventional moving mass train-turnout model are in good agreement. In addition, the new train-turnout coupled model can provide additional track dynamics results. It is concluded that the train-turnout coupled model can provide a more realistic train-turnout dynamic interaction compared to the moving mass train-turnout model.